Arbuscular mycorrhizal fungi suppress ammonia-oxidizing bacteria but not archaea across agricultural soils - Sun, Daquan; Rozmoš, Martin; Kotianová, Michala; Hršelová, Hana; Jansa, Jan (Heliyon, 2024)
Arbuscular mycorrhizal (AM) fungi are supposedly competing with ammonia-oxidizing microorganisms (AO) for soil nitrogen in form of ammonium. Despite a few studies directly addressing AM fungal and AO interactions, mostly in artificial cultivation substrates, it is not yet clear whether AM fungi can effectively suppress AO in field soils containing complex indigenous microbiomes. To fill this knowledge gap, we conducted compartmentalized pot experiments using four pairs of cropland and grassland soils with varying physicochemical properties. To exclude the interference of roots, a fine nylon mesh was used to separate the rhizosphere and mesh bags, with the latter being filled with unsterile field soils. Inoculation of plants with AM fungus Rhizophagus irregularis LPA9 suppressed AO bacteria (AOB) but not archaea (AOA) in the soils, indicating how soil nitrification could be suppressed by AM fungal presence/activity. In addition, in rhizosphere filled with artificial substrate, AM inoculation did suppress both AOB and AOA, implying more complex interactions between roots, AO, and AM fungi. Besides, we also observed that indigenous AM fungi contained in the field soils eventually did colonize the roots of plants behind the root barrier, and that the extent of such colonization was higher if the soil has previously been taken from cropland than from grassland. Despite this, the effect of experimental AM fungal inoculation on suppression of indigenous AOB in the unsterile field soils did not vanish. It seems that studying processes at a finer temporal scale, using larger buffer zones between rhizosphere and mesh bags, and/or detailed characterization of indigenous AM fungal and AO communities would be needed to uncover further details of the biotic interactions between the AM fungi and indigenous soil AO.
Keywords: Ammonia-oxidizing microorganisms (AO); Quantitative real-time PCR (qPCR); Land use; Arbuscular mycorrhizal (AM) fungi; Cropland and grassland; Agricultural soils